Gobiernos Totalitarios - Hernández López, Luz Monserrat (Vida Científica Boletín Científico de la Escuela Preparatoria No. 4, 2025)
Totalitarian governments are those governments that exercise control in a country in an authoritarian and absolute way, by a political party or movement, without restrictions, and imposing a non-democratic and generally one-party system in legality, where freedoms are subordinated to the interests of the government. Some examples of totalitarian governments are: Joseph Stalin, Union of Soviet Socialist Republics Adolf Hitler, Nazi Germany Francisco Franco, Francoism Spain Hirohito, Chinese Communist Party, Benito Mussolini, Italy